Economic assessment of the carbon sequestration potential of plantation forests. Issue 1 (October 2021) - Ivanova, A
Abstract: The goals set by Russia for the implementation of the Paris Agreement on Climate Change Mitigation, taking into account the absorptive capacity of forests, have become an additional incentive for the creation of carbon-saving forest plantations, while the formation of a voluntary carbon market has made it possible to receive income from the sale of carbon from such climate forest projects. However, in the absence of experience in the implementation of such projects in Russia and the long-term return on investment in them, associated with the specifics of forestry and the existing risks of obtaining the final result, it has become an unattractive activity. This problem can be solved by creating carbon-depositing forest plantations using fast-growing seedlings of planting material obtained by innovative biotechnological methods. The study determined the costs of creating 1 hectare of carbon-depositing forest plantations, forecasting the possible additional income from 1 hectare per year from forest plantations for the implementation of net primary production. It is concluded that even with conservative net primary production and low carbon prices, the use of planting material obtained by in vitro clonal micropropagation when creating carbon-depositing forest plantations will reduce the payback period of climate forestry projects to 5 years.